Pengaruh Periklanan dan Promosi Penjualan terhadap Keputusan Pembeli pada Perumahan Asri Residence Jakabaring - Wanda Paula; Mukran Roni (STKIP PGRI SITUBONDO, 2022)
Housing comes with the conveniences offered, the existence of a credit system, low interest offers, booking fees at low prices and so on to attract consumer interest. The Asri Residence Housing Office, located in Jakabaring, strives to attract customer buying interest so that the sale of housing units and properties is in accordance with the company's goals. advertisements designed by the company have not been right on target, it can be seen by frequently distributing such brochures to people who do not need a house. For today's all-digital era, marketing through social media should be maximized with interesting and regular posts. If advertisements are to be successful in influencing consumer behavior, they must first lead consumers through a series of acceptance stages. In addition to advertising to increase sales there is also a sales promotion. Sales promotion tools used by Asri Residence Housing include vouchers, gifts and discounts.